Pengaruh Edukasi Tentang Protokol Kesehatan Terhadap Pengetahuan dan Sikap Pencegahan Penularan Covid-19 pada Anak Usia 10-12 Tahun - Sambo, Mery; Beda, Nikodemus S.; Odilaricha, Yolanda Christiana; Marampa, Litwina (Progres Ilmiah Kesehatan, 2021)
The lack of knowledge and attitudes of children towards health protocols (washing hands, wearing mask, physical distancing) as an effort to prevent COVID-19 is the main factor that causes the incidence of COVID-19 in children to continue and is increasing. So, there is a need for education on health protocols (washing hands, wearing mask, physical distancing) so that children can avoid COVID-19. The purpose of this study was to determine the effect of health protocol education on knowledge and attitudes to prevent COVID-19 transmission in children. This study used a pre-experimental study with a one group pre test-post test design approach. The population in the study was 400 children and the research sample was 78 children aged 10-12 years, which were taken using stratified random sampling technique. The result of the study were analyzed using the Wilcoxon statistical test with a significance level of ?=0,05, the value of p=0,000 was obtained, this shows that there is an effect of health protocol education on knowledge and atitudes to prevent COVID-19 transmission in children aged 10-12 years at Frater Bakti Luhur Elementary School. Providing education has a great impact on increasing knowledge and attitudes.